2012
DOI: 10.1016/j.jss.2012.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in mortality after blunt injury: Does insurance type matter?

Abstract: Background Insurance-related outcomes disparities are well-known, but associations between distinct insurance types and trauma outcomes remain unclear. Prior studies have generally merged various insurance types into broad groups. The purpose of this study is to determine the association of specific insurance types with mortality after blunt injury. Materials and Methods Cases of blunt injury among adults aged 18-64 years with an Injury Severity Score (ISS)>9 were identified using the 2007-2009 National Trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 35 publications
0
42
0
Order By: Relevance
“…Finally, we used this quasi-experimental framework to examine whether the provision had any measureable impact on clinical outcomes that may be plausibly associated with changes in insurance status among trauma patients. 17,19-29,38 For all analyses, we adjusted for facility-level fixed effects and clustered standard errors at the facility level to allow for within-facility correlation. For the subgroup analysis regarding changes in uninsurance, we tested for between subgroup differences in the policy's impact by adding an interaction term between post-period, young adult, the patient subgroup feature of interest.…”
Section: Study Data and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we used this quasi-experimental framework to examine whether the provision had any measureable impact on clinical outcomes that may be plausibly associated with changes in insurance status among trauma patients. 17,19-29,38 For all analyses, we adjusted for facility-level fixed effects and clustered standard errors at the facility level to allow for within-facility correlation. For the subgroup analysis regarding changes in uninsurance, we tested for between subgroup differences in the policy's impact by adding an interaction term between post-period, young adult, the patient subgroup feature of interest.…”
Section: Study Data and Methodsmentioning
confidence: 99%
“…6,7,13 A robust literature based on observational studies documents disparities in health outcomes after trauma between the insured and the uninsured. 15-29 Compared to insured trauma patients, and after controlling for known risk factors at the patient, injury, and facility level, uninsured patients receive less care, 16,17,30 are less likely to undergo a surgical procedure, 17,30 have shorter length of hospital and intensive care unit (ICU) stay, 26,27 have lower rates of discharge to a rehabilitation facility, 18,22,24,27 and have higher in-hospital mortality. 17,19-21,23,26-30 Though some have suggested that these disparities are driven by provider sensitivity to insurance status and subsequent treatment decisions, 17,21,30 the findings to date are limited to suggestive associations since they were all derived from observational data.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies have also found higher odds of mortality in trauma patients who self-pay. 24,25 It could be assumed that adolescents in the self-pay category include uninsured patients, 24 and these adolescents may represent families who do not qualify for public assistance and cannot afford insurance on their own. Adolescents without any type of insurance may have extremely limited access to mental health services, leading to a higher likelihood of longterm untreated mental health issues, and possibly a higher risk of death.…”
Section: Figurementioning
confidence: 99%
“…3,4 Several studies, which examined only a single medical condition, reported variation in the quality of hospital care by insurance type. 5,6 One explanation for the observed difference in quality by insurance type is that uninsured and Medicaid patients tend to use different hospitals than privately insured and Medicare patients do. Hospital characteristics such as ownership, safety-net status, and geographic location thus may be among the key factors that explain differences in quality, rather than patient-level characteristics such as insurance status.…”
mentioning
confidence: 99%